Cofilin Loss in Drosophila Muscles Contributes to Muscle Weakness through Defective Sarcomerogenesis during Muscle Growth - Balakrishnan, Mridula (Cell Rep, 2020)
Sarcomeres, the fundamental contractile units of muscles, are conserved structures composed of actin thin filaments and myosin thick filaments. How sarcomeres are formed and maintained is not well understood. Here, we show that knockdown of Drosophila cofilin (DmCFL), an actin depolymerizing factor, disrupts both sarcomere structure and muscle function. The loss of DmCFL also results in the formation of sarcomeric protein aggregates and impairs sarcomere addition during growth. The activation of the proteasome delays muscle deterioration in our model. Furthermore, we investigate how a point mutation in CFL2 that causes nemaline myopathy (NM) in humans affects CFL function and leads to the muscle phenotypes observed in vivo. Our data provide significant insights to the role of CFLs during sarcomere formation, as well as mechanistic implications for disease progression in NM patients.